The benefits of vocabulary in teaching english to primary school children (Multidisciplinary Journal of Science and Technology, 2024)
This study examines the advantages of integrating vocabulary building activities in teaching English to primary school children. The research explores how enhancing students' vocabulary can improve their language acquisition, comprehension, and communication skills. Through a comprehensive review of literature, the paper highlights the impact of vocabulary instruction on reading fluency, writing proficiency, and overall academic performance in primary school settings. The findings suggest that an enriched vocabulary repertoire not only aids in language development but also fosters cognitive abilities and critical thinking among young learners. This annotation underscores the significance of incorporating vocabulary teaching strategies in English language instruction for primary school children to enhance their linguistic competence and academic success.